Evaluation of Emergency Department-Based Surveillance Systems at 2 Healthcare Facilities After Hurricane Maria: Puerto Rico, 2017-2018. (2023) - Adams, Laura E.; Vargas, Luzeida; Frasqueri-Quintana, Veronica M.; Torres-Figueroa, Xiomara; Ryff, Kyle; Sanchez-Gonzalez, Liliana; Little, Emma; Ciampaglio, Kaitlyn; Reyes Claudio, Julio M.; Ponton-Cruz, Elyonel; Santiago, William; Paz-Bailey, Gabriela; et al.
ABSTRACT: Objectives: Hurricane Maria caused catastrophic damage in Puerto Rico, increasing the risk for morbidity and mortality in the post-impact period. We aimed to establish a syndromic surveillance system to describe the number and type of visits at 2 emergency health-care settings in the same hospital system in Ponce, Puerto Rico. Methods: We implemented a hurricane surveillance system by interviewing patients with a short questionnaire about the reason for visit at a hospital emergency department and associated urgent care clinic in the 6 mo after Hurricane Maria. We then evaluated the system by comparing findings with data from the electronic medical record (EMR) system for the same time period. Results: The hurricane surveillance system captured information from 5116 participants across the 2 sites, representing 17% of all visits captured in the EMR for the same period. Most visits were associated with acute illness/symptoms (79%), followed by injury (11%). The hurricane surveillance and EMR data were similar, proportionally, by sex, age, and visit category. Conclusions: The hurricane surveillance system provided timely and representative data about the number and type of visits at 2 sites. This system, or an adapted version using available electronic data, should be considered in future disaster settings.